Mapping potential nature-based tourism areas by applying GIS-decision making systems in East Azerbaijan Province, Iran. Issue 3 (3rd July 2019) - Ghorbanzadeh, Omid; Pourmoradian, Samereh; Blaschke, Thomas; Feizizadeh, Bakhtiar
ABSTRACT: The northern regions of Iran have a high tourism potential that is currently under-utilized, particularly by local tourists. This area is renowned for its cultural and historical type of tourism. However, its natural landscapes could be introduced as another source of tourism attraction, since its wide range of geographical spaces makes this area suitable for some nature-based recreation activities such as walking, climbing and camping. The authors seek to suggest a methodology for developing maps showing potential areas for nature-based tourism (NBT) based on the natural physical environments. In this paper, NBT is studied from a geographical point of view. NBT provides a break to everyday life by facilitating the enjoyment of nature. In our study, the approach integrates GIS-based multi-criteria decision analysis (MCDA) and the analytical network process (ANP) through ordered weighted average (OWA) for mapping potential NBT areas in East Azerbaijan province, Iran. Relevant factors were selected, implemented as GIS datasets, weighted with ANP, and aggregated with OWA. The analysis produced a map identifying areas with a high potential for NBT, which is informative for tourism managers.